Maximizing the Role of Parents as a Container for Forming Children of the Qur'anic Generation from the Perspective of Surah Al-Luqman - Fatimah Az Zahro; Agnia Alviaturr Rohmaniah; Umar Al Faruq (MAQOLAT: Journal of Islamic Studies, 2024)
Luqman's story and his advice to his son in Surah Luqman highlight the importance of education and the formation of children's character in Islam. Luqman emphasized the importance of faith and moral education as an inseparable unit, by providing a good example as a parent and educator. He taught his children about faith in Allah, giving thanks to Him, and being filial to their parents. Apart from that, Luqman also gets his children used to doing good deeds and being polite in interacting with fellow humans. Luqman's story provides strong guidelines for parents and educators in educating their children well, both academically and spiritually.